Special Interest Politics and Trade Policy – An Empirical Challenge - Carl-Johan Belfrage (Lund University, School of Economics and Management, Department of Economics, 2004)
The model of protectionist support for individual industries as an endogenous outcome of special interest politics pioneered by Grossman and Helpman (1994) is generalized and then empirically examined using data for a number of OECD countries and regions. Cross-sectional regressions are performed on the full sample,as well as on individual countries. The model generally holds up quite well to this empirical challenge. The estimates indicate that equilibrium ratios of special interest to general interest marginal utilities (with respect to protection levels) vary positively with protection levels as the theory has led us to expect. Terms of trade concerns seem important to the larger countries in our sample as implied by the present generalization of the GH model (as well as by the optimum tariff literature), but the influence of downstream interests does not come across in the estimates. The results seem robust also to inclusion of variables reflecting exogenous political concerns (indicated as relevant in other studies), although those bring a substantial addition to predictive power which strengthens the impression that (what is endogenously derived in) the GH model only captures a limited share of the considerations underlying trade policy decisions.
Keywords: F13; 330; Trade policy; Lobbying; Special interest groups